Gastroprotective and ulcer healing effects of essential oil from Hyptis spicigera Lam. (Lamiaceae) - Takayama, Christiane; de-Faria, Felipe Meira; Alves de Almeida, Ana Cristina; Valim-Araujo, Deborah de Arantes e Oliveira; Rehen, Camilla Souza; Dunder, Ricardo Jose; Rabelo Socca, Eduardo Augusto; Manzo, Luis Paulo; Rozza, Ariane Leite [UNESP]; Salvador, Marcos Jose; Pellizzon, Claudia Helena [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; et al. (Elsevier B.V., 2011)
Ethnopharmacological relevance: Hyptis Jacq. (Lamiaceae) is being used in traditional medicine to treat fever, inflammation and gastric disturbances. Hyptis spicigera Lam. is a native plant distributed across the central region of Brazil. The essential oil extracted from this plant is used in folk medicine as antipyretic.Aim of the study: The effects of the essential oil obtained from the aerial parts of Hyptis spicigera (OEH) were evaluated for their gastroprotective and healing activities.Materials and methods: OEH chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS). The gastroprotective action of the OEH was evaluated in rodent experimental models (ethanol and NSAID). To elucidate mechanisms of action, the antisecretory action and involvements of NO, SH, mucus and PGE2 were evaluated. The acetic acid-induced gastric ulcer model and Western Blot assay (COX-2 and EGF) were also used to evaluate the OEH healing capacity.Results: GC-MS analysis of OEH indicated three monoterpenes as major compounds: alpha-pinene (50.8%), cineole (20.3%) and beta-pinene (18.3%) and, at the dose of 100 mg/Kg, p.o., OEH provided effective gastroprotection against lesions induced by absolute ethanol (97%) and NSAID (84%) in rats. OEH do not interfere with H+ secretion in gastric mucosa and its gastric protection does not depend on nitric oxide (NO) and sulfhydryl compounds (SH). The gastroprotective action of OEH occurs due to an increase in the gastric mucus production (28%) induced by PGE2 levels. Furthermore, OEH demonstrated a great healing capacity with 87% of reduction in ulcerative lesion area. It accelerated the healing of acetic acid-induced gastric lesions due to an increase in COX-2 (75%) and EGF (115%) expression in gastric mucosa. No sign of toxicity was observed in this study, considering the analyzed parameters.Conclusions: All these results suggest the efficacy and safety of Hyptis spicigera in combating and healing gastric ulcer. Considering the results, it is suggested that the OEH could probably be a good therapeutic agent for the development of new phytotherapeutic medicine for the treatment of gastric ulcer. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Hyptis spicigera Lam.; Essential oil; Gastric protection; Healing action